Odor-related brain hyper-reactivity in euthymic bipolar disorder: An fMRI and ERP study. (August 2019) - Negoias, Simona; Chen, Ben; Iannilli, Emilia; Ning, Yuping; Kitzler, Hagen H.; Hummel, Thomas; Krüger, Stephanie
Highlight: Patients with euthymic BD responded more vigorously to odors in fMRI and OERPs. Patients with euthymic BD showed normal olfactory function in psychophysical test. The over-activated brain regions were part of olfactory or emotion processing circuits. Abstract: Previous studies on olfactory function in patients with bipolar disorder (BD) are limited and contradictory. The current study aimed to comprehensively analyze the olfactory function of patients with euthymic BD using psychophysical, electrophysiological and neuroimaging techniques. Twenty-one patients with BD in remission and 20 healthy controls were tested with the "Sniffin' Sticks" olfactory test. Block-design fMRI data to a pleasant and an unpleasant stimulus were acquired while recording intensity and hedonic ratings. Olfactory event-related potentials (OERP) to the same stimuli were additionally recorded. Results show no differences between patients and healthy controls in terms of self-rated olfactory function and tested olfactory domains (odor threshold, discrimination or identification) ( p >0.05). Compared to healthy controls, patients showed an increased fMRI activation in multiple cortical and subcortical regions as a response to olfactory stimulation, as well as larger amplitudes of OERPs regardless of the hedonic valence of the odor. All in all, patients with euthymic BD showed a stronger central responsiveness to odorous stimuli in fMRI and OERPs despite of normal psychophysical results, indicating the probable existence of an odor-related over-reactive brain network in the remission phase of BD.